2011
DOI: 10.5402/2011/513503
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Post-Thrombotic Syndrome: The Effect of Recurrent Venous Thrombosis and Inherited Thrombophilia

Abstract: Post-thrombotic syndrome is an important chronic complication of deep vein thrombosis. This syndrome can be debilitating to patients and has a major economic impact on health care services. The pathophysiology of post-thrombotic syndrome is currently incompletely understood. Because therapeutic options for post-thrombotic syndrome are extremely limited and results are often disappointing, recognizing of the pathophysiology and risk factors of this syndrome is essential to prevent the disabling consequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…In some countries with high prevalence of prothrombotic genetic polymorphism, thrombophilia was reported to be the second most common cause of VTE [ 14 ]. Recent studies suggested that thrombophilia not only predisposes to the development of venous thrombosis but also seems to interfere in the development of postthrombotic syndrome either directly by prolonging residual venous thrombosis or indirectly by increasing venous thrombotic recurrence rate [ 27 , 28 ]. Assessment for genetic risk factors for VTE allows to avoid thrombogenic treatment (estroprogestative treatment) and to prevent venous thrombosis in high risk conditions (pregnancy, trauma, surgery, and long-haul air travel) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some countries with high prevalence of prothrombotic genetic polymorphism, thrombophilia was reported to be the second most common cause of VTE [ 14 ]. Recent studies suggested that thrombophilia not only predisposes to the development of venous thrombosis but also seems to interfere in the development of postthrombotic syndrome either directly by prolonging residual venous thrombosis or indirectly by increasing venous thrombotic recurrence rate [ 27 , 28 ]. Assessment for genetic risk factors for VTE allows to avoid thrombogenic treatment (estroprogestative treatment) and to prevent venous thrombosis in high risk conditions (pregnancy, trauma, surgery, and long-haul air travel) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subacute inflammatory reaction in thrombus resolution spreads to the vessel wall with leukocyte influx and vessel wall remodeling, ultimately leaving behind a thickened, fibrotic, and noncompliant vein wall with incompetent valvular function . Perivenous and mural fibrosis extend beyond thrombosed segments affecting adjacent segments of valve cusps, but inducing secondary reflux . The prevalence of venous reflux increases over time and plateaus after 1–2 years .…”
Section: Pathomechanisms Of Nonresolving Thrombi and Ptsmentioning
confidence: 99%
“…Chronic venous insufficiency, post-thrombotic syndrome (PTS) and pulmonary embolism (PE) are the main complications of DVT. 1 The traditional venous anatomy of the LLs has been described as a continuous flow of veins without duplication. 2 However, recent studies based on duplex ultrasonography, venography and cadavers have demonstrated variations in the anatomy of the venous system of the lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic venous insufficiency, post-thrombotic syndrome (PTS) and pulmonary embolism (PE) are the main complications of DVT. 1…”
Section: Introductionmentioning
confidence: 99%